Transformasi Digital dan Perlindungan Konsumen: Optimalisasi Peran BPKN dalam Menghadapi Ekonomi Digital - Vicky Fernando; Antoni Ludfi Arifin (Bulletin of Community Engagement, 2026)
Digital transformation has significantly changed consumption patterns, economic transactions, and the relationship between consumers and business actors. The rapid development of digital platforms, electronic commerce, and electronic payment systems has accelerated the growth of the digital economy in Indonesia. However, this development also introduces new challenges in consumer protection, including information asymmetry, misuse of personal data, and the increasing risk of fraud in online transactions. This study aims to analyze how digital transformation can optimize the role of the National Consumer Protection Agency/Badan Perlindungan Konsumen Nasional (BPKN) in addressing the dynamics of the digital economy. The research employs a qualitative approach using a literature review method based on academic journal articles, scholarly books, and policy documents related to digital economy and consumer protection. The analysis was conducted through literature identification, thematic analysis, and conceptual synthesis. The findings indicate that the existing consumer protection regulations have not fully accommodated the complexity of digital transactions, thus requiring regulatory strengthening and institutional transformation. Digital transformation within BPKN, including the use of integrated digital complaint systems, big data analytics, and artificial intelligence technology, can enhance supervisory effectiveness, accelerate consumer dispute resolution, and improve public services. Therefore, optimizing BPKN through digital transformation is expected to create a more adaptive, transparent, and responsive consumer protection system in Indonesia’s digital economy.